A small-molecule inhibitor of MDMX suppresses cervical cancer cells via the inhibition of E6-E6AP-p53 axis. (March 2022) - Zhang, Jingwen; Yu, Guohua; Yang, Yanting; Wang, Yingjie; Guo, Mengqi; Yin, Qikun; Yan, Chunhong; Tian, Jingwei; Fu, Fenghua; Wang, Hongbo
Abstract: Dysfunction of p53 is observed in many malignant tumors, which is related to cancer susceptibility. In cervical cancer, p53 is primarily degradated through the complex of high-risk human papillomaviruses (HPV) oncoprotein E6 and E6-associated protein (E6AP) ubiquitin ligase. What is less clear is the mechanism and role of murine double minute X (MDMX) in cervical carcinogenesis due to the inactive status of murine double minute 2 (MDM2). In the current study, XI-011 (NSC146109), a small-molecule inhibitor of MDMX, showed robust anti-proliferation activity against several cervical cancer cell lines. XI-011 promoted apoptosis of cervical cancer cells via stabilizing p53 and activating its transcription activity. Moreover, XI-011 inhibited the growth of xenograft tumor in HeLa tumor-bearing mice, as well as enhanced the cytotoxic activity of cisplatin both in vitro and in vivo . Interestingly, MDMX co-localized with E6AP and seems to be a novel binding partner of E6AP to promote p53 ubiquitination. In conclusion, this work revealed a novel mechanism of ubiquitin-dependent p53 degredation via MDMX-E6AP axis in cervical carcinogenesis, and offered the first evidence that MDMX could be a viable drug target for the treatment of cervical cancer. Graphical Abstract: ga1 Highlights: XI-011 inhibits the proliferation and induces apoptosis of cervical cancer cells via increasing the p53 stability and its transactivation. XI-011 potentiates the antitumor activity of cisplatin in vitro and in vivo . Mdmx is one novel binding partner of E6AP to promote p53 ubiquitination in cervical cancer. MDMX could be a novel drug development strategy for the treatment of human cervical cancer.